Rare earth doped lead-free germanate glasses for modern photonics - Janek, Joanna; Pisarska, Joanna; Pisarski, Wojciech (Photonics Letters of Poland, 2014)
Lead-free germanate glasses doped with rare earth ions were synthesized and next studied using excitation and luminescence spectroscopy. Rare earths were limited to Pr3+, Eu3+ and Er3+ ions. Several luminescence bands correspond to transitions originating from the 3P0 and 1D2 states of Pr3+, the 5D0 state of Eu3+, the 4S3/2, 4F9/2 and 4I13/2 states of Er3+, respectively. The relatively long lifetime for the upper 4I13/2 laser state of Er3+ suggest that lead-free germanate glasses are promising materials for near-infrared optical amplifiers. Full Text: PDF References M. Yamane and Y. Asahara, Glasses for photonics (Cambridge University Press 2000). CrossRef A. Jha et al, "Rare-earth ion doped TeO2 and GeO2 glasses as laser materials", Prog. Mater. Sci. 57, 1426 (2012). CrossRef J.S. Wang, E.M. Vogel, E. Snitzer, "Tellurite glass: a new candidate for fiber devices", Opt. Mater. 3, 187 (1994). CrossRef J. Dorosz, "Optical Fibers Technology", Ceramics 86 (2005). J. Dorosz, R.S. Romaniuk, "Development of Optical Fiber Technology in Poland", INTL J. Electron. Telecom. 57, 191 (2011). CrossRef M. Kochanowicz, W. Mazerski, J. Żmojda, K. Czajkowski, D. Dorosz, "Green upconversion emission in tellurite optical fibre codoped with Yb3+/Er3+", Phot. Lett. Poland 5, 35 (2013). CrossRef J. Żmojda, D. Dorosz, M. Kochanowicz, J. Dorosz, "Spectroscopic properties of Yb3+/Er3+ - doped antimony-phosphate glasses for fiber amplifiers", Phot. Lett. Poland 2, 76 (2010). CrossRef H. Lin, E.Y.B. Pun, B.J. Chen, Y.Y. Zhang, "Rare-earth ion doped lead- and cadmium-free bismuthate glasses", J. Appl. Phys. 103, 056103 (2008). CrossRef S.S. Bayya, G.D. Chin, J.S. Sanghera, I.D. Aggarwal, "Germanate glass as a window for high energy laser systems", Opt. Express 14, 11687 (2006). CrossRef J.M. Jewell, P.L. Higby, I.D. Aggarwal, "Properties of BaO–R2O3– Ga2O3–GeO2 (R = Y, Al, La, and Gd) Glasses", J. Am. Ceram. Soc. 77, 697 (1994). CrossRef R.R. Xu, Y. Tian, M. Wang, L.L. Hu, J.J. Zhang, "Spectroscopic properties of 1.8 μm emission of thulium ions in germanate glass", Appl. Phys. B 102, 109 (2011). CrossRef R. Xu, Y. Tian, L. Hu, J. Zhang, "Broadband 2 μm emission and energy-transfer properties of thulium-doped oxyfluoride germanate glass fiber", Appl. Phys. B 104, 839 (2011). CrossRef V.K. Tikhomirov, S.A. Tikhomirova, "Hypersensitive transition 3P0 → 3F2 of Pr3+ related to the polarizability and structure of glass host", J. Non-Cryst. Solids 274, 50 (2000). CrossRef R. Balda, A. Oleaga, J. Fernandez, J.M. Fdez-Navarro, "Spectroscopy and frequency upconversion of Er3+ ions in lead niobium germanate glasses", Opt. Mater. 24, 83 (2003). CrossRef H. Yamauchi, Y. Ohishi, "Spectroscopic properties of Er3+-doped PbO–Ga2O3–GeO2 glass for optical amplifiers", Opt. Mater. 27, 679 (2005). CrossRef W.A. Pisarski, Ł. Grobelny, J. Pisarska, R. Lisiecki, and W. Ryba-Romanowski, "Spectroscopic properties of Yb3+ and Er3+ ions in heavy metal glasses", J. Alloys Compd. 509, 8088 (2011). CrossRef